Diastolic Heart Murmur, Nocturnal Back Pain, and Lumbar Rigidity in a 7-Year Girl: An Unusual Manifestation of Lyme Disease in Childhood - Genn Kameda; Silvia Vieker; Johannes Hartmann; Tim Niehues; Alfred Längler (Case Reports in Pediatrics)
A 7-year-old girl presented with nocturnal pain in her back and legs. The physical examination revealed a loud opening sound of the mitral valve and lumbar rigidity. With the exception of significantly increased anti-nuclear antibody (ANA) levels, the immunological findings did not show any other abnormal parameters, also spinal magnetic resonance imaging (MRI) and ultrasound examination of the abdomen and pelvis yield no pathological findings. The lumbar puncture showed a lymphocytic pleocytosis as well as an intrathecal synthesis of Borrelia-specific antibodies. Echocardiography showed a thickened mitral valve with mild regurgitation. No other signs of florid endocarditis or myocarditis could be detected. Due to these findings, the diagnosis Lyme neuroborreliosis was made and an intravenous antibiotic therapy was given. The clinical symptoms subsided. Six months later, she had an almost normal mitral valve with only trivial mitral insufficiency. The association between the lumbar rigidity and the thickened mitral valve remains unclear. The case of our patient with nocturnal back and leg pain may be considered a rare case of Lyme neuroborreliosis with meningoradiculitis in children, and to our knowledge these symptoms together with cardiac involvement, such as a significantly thickened mitral valve, have not yet been described in the literature.